MODERN COMPETENCES OF ORGANIZING TECHNOLOGY COURSES - Bakhronova Shakhlo Islamovna; Davlatova Nasiba Ubaidilloyevna; Pirimova Norjona (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article provides information about the essence, content and directions of modern competences in the organization of classes in technology.